Estimating the recreational use value of Tis-Abay Waterfall in the upstream of the Blue Nile River, North-West Ethiopia. Issue 12 (December 2022) - Wubalem, Atalel; Reynolds, Travis W.; Wodaju, Amare
Abstract: Tis-Abay Waterfall is a famous tourist destination in northern Ethiopia, attracting both domestic and international visitors. Although the site's recreation and tourism potential are enormous, the value of the waterfall remains underestimated; an application of economic valuation methods can provide information to better utilize the resource. This study estimates the recreational value of Tis-Abay Waterfall and analyzes the consumer characteristics associated with recreational demand. Drawing on data from 1044 on-site surveys, the study uses the Individual Travel Cost Method (ITCM) with a Zero-Truncated Poisson (ZTP) regression model. Results of the ZTP regression suggest that visitors' age, monthly income, and interest in alternative recreation sites like Lake Tana and Gondar Fasiledes Royal Castle are variables significantly and positively related with recreational demand for the Tis-Abay Waterfall. However, visitors' recreational demand is negatively associated with respondents' distance from the site, leisure time, and total cost of site access. The appraisal suggests that the Tis-Abay Waterfall has a significant annual recreational value of 9.5 million. But it also shows that the waterfall's value would increase significantly, up to 17.3 million, with hypothetical quality improvements in the waterfall settings. The value attachment suggests that estimating the recreation value for Tis-Abay Waterfall is a central component in the sustainable use and management of the resource. However, the presence of unfavorable trade-offs with the electric power plant and the inadequate infrastructure and services for reaching the site are major concerns that require immediate attention to make better use of Tis-Abay Waterfall's recreational services. Abstract : Economic valuation; Recreational value; Tis-Abay Waterfall; Individual travel cost; Zero-truncated; Consumer surplus